Water Solubility and Physical Losses and Sulfur and Phosphorus from S-Coated Triple Superphosphates - DANA, MADE (AGRITROP, 2007)
Coated fertilizer must retain the coating during transport and handling, but the nutrients in the coat must bereleased readily in the soil to meet plant demand. Three experimental fertilizer where S is adhered to TSP granulesusing AD1, AD3 or AD2 adhesive were compared with a commercial S coated TSP, Hifert (HF) Goldphos-10.Fertilizer S loss from the granule was measured in a rotating drum friabilator. The highest particle loss was recordedwit HF, and there were no significant differences recorded between AD1, AD2 and AD3. Release of S from the coatedfertilizers was measured by placing the fertilizers between 500 pm nylon mesh and leaching with distilled waterat 20 mL min-1 for up to 96 h. In all release was fastest from AD1 and AD3, and the amount of Ca and P releasedfrom the granule was also highest with these two products. Granules were scanned in the electron microscope, andelectron microprobe both before and after leaching. Dispersion in distilled water was also recorded. The microprobescan confirmed the leaching data with more S remaining in the granule with HF than AD1 or AD3. These dataconfirm earlier studies that the method of adhesion of S to TSP can markedly alter the agronomic performance ofthe fertilizer.